Do People Who Believe in God Report More Meaning in Their Lives? The Existential Effects of Belief - Cranney, Stephen (2013)
I conduct the first large-N study explicitly exploring the association between belief in God and sense of purpose in life. This relationship, while often discussed informally, has received little empirical attention. Here I use the General Social Survey to investigate how form of and confidence in belief in God is related to sense of purpose in life, as measured by a Likert item level of agreement with the statement “In my opinion, life does not serve any purpose.” Using logistic regression analysis, I find that those who indicate that they are confident in God's existence report a higher sense of purpose compared to nonbelievers, believers in a higher power, and those who believe but occasionally doubt.